Synoptic analysis of a cold period in Bauru-SP in July 2015 - Capucin, Bruno César [UNESP]; Llopart, Marta [UNESP]; Reboita, Michelle Simões; Iwabe, Clara Miho Narukawa [UNESP] (Universidade Federal do Rio de Janeiro, 2019)
The first ten days of July 2015 in Bauru, SP, presented low temperatures with a higher decline on day 05. The purpose of this study was to describe the atmosphere characteristics that led to this decline in air temperature on July 5th. For this, we used the ERA-Interim reanalysis data with horizontal resolution of 0.75 ° x 0.75 °. Synoptic charts were constructed and analyzed from 2 days before to 2 days after the day of interest; other atmospheric fields were analized as well. In the period prior to the highest temperature drop in Bauru, there is a wave in the west flow at 500 hPa that propagates through the South Pacific Ocean. When this system crosses the Andes, the formation of the frontal surface wave occurs that, together with the anticyclone migratory species cause horizontal advection of the cold air mass that influenced the time in much of Brazil in the beginning of July 2015. Considering the wave pattern at 500 hPa, the amplification of the ridge by the intense hot advection on the southwest side of the high post (positive) to the east of the dug (crest) and the low values of potential vorticity in the area of the dug had participation in the slow displacement of the wave, which contributed to the greater permanence of the post-frontal discharge in the Atlantic Ocean and, therefore, for a predominance of the transport of cooler air towards the interior of the State of São Paulo.
Análise Sinótica de um Período Frio Em Bauru - Sp em Julho de 2015
Keywords: Bauru; Cold wave; Synoptic analysis